2014
DOI: 10.1177/0009922814553432
|View full text |Cite
|
Sign up to set email alerts
|

Brief Training in Patient-Centered Counseling for Healthy Weight Management Increases Counseling Self-efficacy and Goal Setting Among Pediatric Primary Care Providers

Abstract: Brief training in patient-centered counseling appears to increase self-efficacy and the frequency and quality of weight-related counseling provided by PCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…The results from the current study support prior evaluations of interventions aiming to increase weight-related counseling among physicians [20,21]. A 2015 study assessed only the provider training program component of the Strong4Life Healthy Weight Counseling MOC six- and 12-months after training, and reported high BMI percentile plotting before and after training [21]. In contrast to the current study, the prior study reported goal-setting frequency of 4% at baseline which increased to 58% 12 months after training (versus 84% six months after MOC completion in the current study).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results from the current study support prior evaluations of interventions aiming to increase weight-related counseling among physicians [20,21]. A 2015 study assessed only the provider training program component of the Strong4Life Healthy Weight Counseling MOC six- and 12-months after training, and reported high BMI percentile plotting before and after training [21]. In contrast to the current study, the prior study reported goal-setting frequency of 4% at baseline which increased to 58% 12 months after training (versus 84% six months after MOC completion in the current study).…”
Section: Discussionsupporting
confidence: 85%
“…The six-month Strong4Life Healthy Weight Counseling MOC program included five components: 1) an in-person, 2-hour Strong4Life training highlighting recommended counseling strategies and the need for pediatricians to discuss evidenced-based strategies for healthy weight (“health messages”) with patients and their parents; 2) a one-hour refresher webcast at approximately the third month of the MOC; 3) recommended updates to well-child visit forms to prompt health messaging; 4) peer reviews of patient charts; and 5) two in-practice meetings between clinical and office staff first to review changes to forms in the clinic and subsequently, to assess problem areas in counseling practices. The Strong4Life training has been previously described (http://www.strong4life.com) [21]. Briefly, trainings were held in groups (average size=12±9 pediatricians) at multiple conference rooms throughout Georgia to facilitate pediatrician participation.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] Despite growing recognition of the value of patient-centred care, evaluation of the published literature indicates that relatively little guidance is available on the use of patient-centred care strategies for the management of obesity. 11 Additionally, within the sparse data on patient-centred care for obesity, most literature focuses on prevention of obesity, often in childhood and adolescence, [12][13][14] with minimal emphasis on patient-centred approaches to obesity management in adults. However, patient-centred care is valuable as patient engagement throughout the decision-making process may lead to increased uptake and more favourable outcomes.…”
mentioning
confidence: 99%
“…In regards to self-efficacy, we found that pediatricians who reported higher self-efficacy, irrespective of survey vignette type, had higher odds of counseling on weight-related topics at well visits. Prior studies have aimed to leverage the association between self-efficacy and practices, by using targeted education and training interventions to improve physician self-efficacy and ultimately increase desired practices (Welsh et al, 2015). Welsh et al examined the use of a brief training session in patient-centered counseling to improve pediatrician self-efficacy around weight management and found it effective for increasing self-efficacy and significantly increasing the documentation of weight counseling at 6-months and 12-months post-training (Welsh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%